2019
DOI: 10.1519/ssc.0000000000000477
|View full text |Cite
|
Sign up to set email alerts
|

CSCCa and NSCA Joint Consensus Guidelines for Transition Periods: Safe Return to Training Following Inactivity

Abstract: We also thank all the athletes, families, coaches, athletic trainers, medical providers, school staff, state associations, researchers, journalists, and others who have participated in this research and have shared information with the NCCSIR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 117 publications
1
45
0
4
Order By: Relevance
“…The drop from peak in AC across the pre-season decreased the population’s competitive season physiological potential and was unable to recover from the decrease throughout the competitive season (B4–B5). The training load athletes experience throughout the competitive season while lacking recovery can put athletes at risk for unnecessary fatigue [ 4 ] (inability to recover from training stress), increased risk of injury [ 6 , 36 ] along with suppression of training adaptations which include AC [ 1 , 6 , 27 ]. Therefore, the spring season preparatory training represents a pivotal opportunity that can positively or negatively affect competitive season performance with little opportunity to reverse unintended consequences.…”
Section: Discussionmentioning
confidence: 99%
“…The drop from peak in AC across the pre-season decreased the population’s competitive season physiological potential and was unable to recover from the decrease throughout the competitive season (B4–B5). The training load athletes experience throughout the competitive season while lacking recovery can put athletes at risk for unnecessary fatigue [ 4 ] (inability to recover from training stress), increased risk of injury [ 6 , 36 ] along with suppression of training adaptations which include AC [ 1 , 6 , 27 ]. Therefore, the spring season preparatory training represents a pivotal opportunity that can positively or negatively affect competitive season performance with little opportunity to reverse unintended consequences.…”
Section: Discussionmentioning
confidence: 99%
“…Although gradual training overload including high-intensity exercise bouts are necessary and self-evident as part of the return-to-competition process, as long as COVID-19 vaccines remains to be revealed and unfolded, careful attention should be given to the introduction of "accumulation training phases" given that prolonged periods of high-volume and high-intensity training may adversely increase the risk of illness among athletes (Nieman and Wentz, 2019;Corsini et al, 2020). Even when the WHO may announce a gradual regression of their containment policies, as supported by a sustained reduction in the number of new infections, hospitalizations, and having sufficient nationwide supply of COVID-19 testing kits, strength and conditioning coaches should still remain alert for potential risk of injury (Corsini et al, 2020) for the following reasons: almost 60% of non-contact injuries have been reported during periods in which collegiate athletes transitioned back into training following a period of inactivity (e.g., after vacation) (Caterisano et al, 2019); cardiac atrophy may occur as soon as 4 weeks of detraining (Pelliccia et al, 2002;Pedlar et al, 2017); an overall loss of 10% of fitness for each week of total inactivity can be generally expected (Eirale et al, 2020); loss of lean mass and muscle strength represent an important injury risk factor (Casa et al, 2012); and the risk for serious injury, and death after a period of inactivity is well-documented (Casa et al, 2012;Caterisano et al, 2019). Recognizing the potential risks involved with reduced training, incorporating cross-training , sprint training (Joo, 2018), and high-intensity interval (HIIT) training sessions (5 bouts of 4 min on 87-97% peak heart rate) every second week of the "at-home period" may aid in the preservation of the athlete's threshold to transport and use oxygen during physical activity (VO2 max ) and repeated sprint ability (RSA), as previously demonstrated in soccer athletes (Slettaløkken and Rønnestad, 2014;Joo, 2018), and in turn, minimize the potential drop-off in cardiorespiratory fitness as a potential consequence of the COVID-19 pandemic.…”
Section: Unique Opportunities For Team-sport Players Periodizationmentioning
confidence: 99%
“…This is true for athletes who have had COVID-19 to any degree. In the initial phases of return to exercise after recovery from mild infection, we recommend a gradual guided activity modification plan such as the 50/30/20/10 rule developed by the National Strength and Conditioning Association and Collegiate Strength and Conditioning Coaches Association Joint committee for use over a 4-week period [6]. The conditioning volume for the first week is reduced by at least 50% of the normal exercise load, followed by 30%, 20%, and 10% in the following 3 weeks if comfortable at the end of each week.…”
Section: Considerationsmentioning
confidence: 99%
“…The conditioning volume for the first week is reduced by at least 50% of the normal exercise load, followed by 30%, 20%, and 10% in the following 3 weeks if comfortable at the end of each week. This would be adjusted by the severity of the disease and may require a graduated return to activity occurring over many months rather than weeks [6].…”
Section: Considerationsmentioning
confidence: 99%